Educational tools for the online teaching of translation and interpreting studies - Tello Fons, Isabel; Valero Doménech, Esperanza (Estudios de Traducción, 2017)
Our study will focus on studying the didactic tools the universities in Spain use to convey the teaching of online translation studies. We will carry out a comparative analysis of the systems and a description of the methodological challenges of online translation teaching.In particular, we aim at analysing the didactic applications of different LMS –learning management systems– for translation teaching. We will go over synchronous and asynchronous, audio-visual and interactive tools such as Moodle, Blackboard Learn and Collaborate or WebCT, among others. They will be analysed from the point of view of the didactics of translation. Some day-to-day case studies in the translation classroom will be addressed as well. We finally will launch a debate on the future scenario of e-learning in Translation and Interpreting.
Keywords: e-learning; LMS systems; didactics of Translation and Interpreting; Blackboard.